Splenic Stromal Cells from Aged Mice Produce Higher Levels of IL-6 Compared to Young Mice - Jihyun Park; Takuya Miyakawa; Aya Shiokawa; Haruyo Nakajima-Adachi; Masaru Tanokura; Satoshi Hachimura (Mediators of Inflammation)
Inflamm-aging indicates the chronic inflammatory state resulting from increased secretion of proinflammatory cytokines and mediators such as IL-6 in the elderly. Our principle objective was to identify cell types that were affected with aging concerning IL-6 secretion in the murine model. We compared IL-6 production in spleen cells from both young and aged mice and isolated several types of cells from spleen and investigated IL-6 mRNA expression and protein production. IL-6 protein productions in cultured stromal cells from aged mice spleen were significantly high compared to young mice upon LPS stimulation. IL-6 mRNA expression level of freshly isolated stromal cells from aged mice was high compared to young mice. Furthermore, stromal cells of aged mice highly expressed IL-6 mRNA after LPS injection in vivo. These results suggest that stromal cells play a role in producing IL-6 in aged mice and imply that they contribute to the chronic inflammatory condition in the elderly.